The Covid-19 in African and Asian Drylands Project: preliminary findings (COST Action 16233 Core Group meeting, Indemini, Switzerland) - Roque de Pinho, Joana (Drylands Facing Change COST Action CA16233 Core group meeting, 2020)
The CONVERGE Covid-19 in African and Asian Drylands Project: preliminary findings. COST Action 16233 Core group meeting, Indemini, Switzerland. August 31 – 4 September 2020